Preparação e caracterização de microesfera de etilcelulose com o ativo metformina - Farias, Alessandra Zucunelli (2023)
The present work describes the preparation and characterization of the formation of microspheres using the polymer ethylcellulose with the drug metformin. Due to the increase in the search for this form of administration for medicines where the demand is to achieve a prolonged release of the drug and the protection of the substance mainly from degradation. The in vitro evaluation carried out using spectroscopic techniques of ethylcellulose microspheres with the drug metformin demonstrated promising characteristics for the percentages of 3 and 5% where release monitoring showed prolonged behavior for the drug.